GAMBARAN PENCARIAN IDENTITAS AGAMA PADA MAHASISWA DI MASA REMAJA AKHIR DENGAN ORANG TUA BERBEDA AGAMA - Novi Franscelia; Untung Subroto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
Religious identity refers to an individual's understanding and acknowledgment of the religion they adhere to, which includes beliefs, practices, values, and symbols associated with that religion. Religious identity reflects how individuals recognize themselves within a religious context, both in relation to God, others, and the world around them. This study aims to describe the process of religious identity exploration among young adults in late adolescence with parents from different religious backgrounds. Using a qualitative method with a phenomenological approach, this research involved six participants aged 18 to 22 from families with religious differences. Data collection was conducted through interviews and observations. The findings show that the process of religious identity formation in adolescents occurs in two main phases: exploration and commitment. In the exploration phase, adolescents seek knowledge and information about religion through reading, discussing, and participating in seminars, which is influenced by interactions with family and social environments, particularly in participants B, C, and E. The commitment phase is characterized by making decisions about the religion they will follow, supported by involvement in religious activities, emotional support, and identification with significant figures, as seen in participants A, D, and F. Open communication with parents plays a significant role in supporting religious exploration and commitment, while conflicts with parents can lead to anxiety that hinders the commitment process. This study provides an overview of the dynamics of religious identity exploration among adolescents growing up in families with religious differences.